Waste management at Tatah Mesjid village used garbage can - sri rahayu (UMBanjarmasin, 2022)
Waste problems are becoming more complicated because of poor waste management. Starting from the problem of temporary shelter, collection, transportation to the place of disposal and processing. Tatah Mesjid Village, located in Alalak District, has problems related to waste, where people are accustomed to throwing garbage into the river. Community service focused on providing trash bins in strategic locations to help people get used to disposing of waste in its place. Trash bins made of plastic are equipped with lids, so they can prevent odors or become a breeding ground for disease-causing animals. Trash cans are placed in village halls and schools. This activity has a positive influence on the surrounding community and also helps village officials in trying to clean the village environment